A Checklist of the Seaweeds of the Mediterranean and Atlantic Coasts of Morocco. II. Phaeophyceae - Benhissoune, S.; Boudouresque, C.-F.; Verlaque, M. (Botanica marina, 2002)
A checklist of Moroccan marine brown algae, based on both literature records and some original data, is given. The distribution of each taxon for this region (12 Mediterranean and 27 Atlantic localities) is reported. Using present-day taxonomy, 131 species, infraspecific taxa and life-history phases are accepted for the Moroccan coasts.